Synthesis of fatty monoester lubricant base oil catalyzed by Fe-Zn double-metal cyanide complex - Raut, Ravindra K.; Shaikh, Mehejabeen; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fatty monoester lubricant base oils as high as 96.7 mol% were prepared by reacting methyl oleate with long-chain alcohols viz., 2-ethyl-1-hexanol (C-8-OH), 1-decanol (C10OH) and 1-dodecanol (C12OH) in the presence of a solid Fe-Zn double-metal cyanide (DMC) complex catalyst. Unlike many other acid catalysts, DMC doesn't produce undesired ether side products. The catalyst was reusable in four recycling experiments with little loss in catalytic activity and ester yield. The long-chain esters prepared in the study have the desired physical properties for their application as lubricant base oils.
Keywords: Fatty monoester; Fe-Zn double-metal cyanide (DMC) catalyst; lubricant base oil; transesterification